PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DI KOTA SAMARINDA - . Yuniarti; Chatas Teguh Prakoso (Magister Administrasi Publik FISIP Universitas Mulawarman, 2018)
Since it have been implemented as an obligation to companies either public or private, Corporate Social Responsibility (CSR) have been becoming potential source for development program funding in Samarinda. This article explains the implementation of CSR in Samarinda, and the cooperation between government, company and society within it. CSR implementation in Samarinda have conformed to several provisions under the Local Regulation Samarinda City Number 3, 2013 about Corporate Social Responsibility. Cooperation between government, company and society described mutual partnership governance. However, the weakness of the regulation implementation resulted in company’s reluctance to fulfil it. On the other hand, the society itself had not utilized CSR to full potential.Keyword: CSR, governance, cooperation between parties